2015
DOI: 10.1186/s13071-014-0526-2
|View full text |Cite
|
Sign up to set email alerts
|

Search for blood or water is influenced by Borrelia burgdorferi in Ixodes ricinus

Abstract: An increasing number of studies suggest that vector-borne parasites are able to alter phenotypic traits in their arthropod vectors so that microorganism transmission is enhanced. This review documents this phenomenon, which occurs between Borrelia burgdorferi bacteria, the causative agents of Lyme borreliosis, and their tick vectors belonging to the Ixodes ricinus complex. It also reviews the influence of other tick-borne pathogens on these ticks. Ticks belonging to the Ixodes ricinus complex benefit from Borr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 70 publications
(114 reference statements)
2
52
0
3
Order By: Relevance
“…Summer camps take place in July or August. While hazard may be reduced at this time as it falls between the two peaks of activity (spring and autumn) (Herrmann and Gern, 2015), exposure for scouts is non-negligible when outdoor living is practiced for a full fortnight. Also, the spring and autumn peaks are not always observed and abundance can be fairly stable across seasons (Randolph et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Summer camps take place in July or August. While hazard may be reduced at this time as it falls between the two peaks of activity (spring and autumn) (Herrmann and Gern, 2015), exposure for scouts is non-negligible when outdoor living is practiced for a full fortnight. Also, the spring and autumn peaks are not always observed and abundance can be fairly stable across seasons (Randolph et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which anti-tick immunity reduces tick fitness is that it impairs tick blood feeding and therefore reduces the quality and quantity of the blood meal (21). With respect to body size, previous studies on I. ricinus have shown that larger nymphs have higher fat reserves (46) and that such nymphs can quest for longer periods of time, which increases their chances of finding a host in the field (9, 47, 48). Body size also influences female fecundity, with larger female ticks laying larger clutches of eggs (49).…”
Section: Discussionmentioning
confidence: 99%
“…Specificity is shown by the fact that many vector-borne pathogens are only effectively acquired and transmitted by one or a few closely related vector species (4-6). Examples of adaptive complexity in pathogens include increasing the vector’s production of immunosuppressive saliva molecules to enhance their own transmission (7), protecting the vector against changes in the environment (8, 9), and manipulating the odor profile of the vertebrate host to increase host-vector encounter rates and pathogen transmission (10-12). Thus, whenever it suits their interests, we expect vector-borne pathogens to enhance the fitness of their arthropod vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Bu kenelerin yayılım alanlarının iklim değişikliğinin etkisiyle oluşan daha sıcak ve kuru hava ile artacağından endişe edilmektedir. ABD'de vektör olan kene türlerinden Ixodes persulcatus aynı zamanda babesiyoz ve insan anaplazmoz etkenlerini taşırken, Avrupa ve Asya'da hakim olan vektör kene türlerinden Ixodes ricinus ve Ixodes persulcatus LH'nın yanı sıra kene kaynaklı ensefalit etkenlerini taşıyabilmektedir [8] .…”
Section: Epidemiyolojiunclassified
“…ABD'de 2014 yılında 25,359 olgu doğrulanmış olarak, 8,102 olgu da olası olgu olarak bildirilmiştir [9] . Avrupa'da en fazla olgu saptanan bölge ise iç Avrupa kıtası ve İskandinavya'dır [1,8] .…”
Section: Epidemiyolojiunclassified